Recovery of carbon fibre from waste prepreg via microwave pyrolysis - Hao, Siqi; He, Lizhe; Liu, Jiaqi; Liu, Yuhao; Rudd, Chris; Liu, Xiaoling (MDPI AG, 2021)
Management of waste from carbon fibre composites has become a significant societal issue as the application of composite grows across many industries. In this study, carbon fibres (CF) were successfully recovered from cured carbon fibre/epoxy (CF/EP) prepreg under microwave pyrolysis at 450, 550 and 650◦ C followed by oxidation of any residual char. The recovered fibres were investigated for their tensile properties, surface morphologies and the elements/functional groups presented on the surface. The chemical compositions of gaseous and oil pyrolysis products were also analysed. The microwave pyrolysis effectively pyrolyzed the epoxy (EP) resin. Char residue remained on the fibre surface and the amount of char reduced as the pyrolysis temperature increased. Compared to virgin fibres, the recovered fibre suffered from a strength reduction by less than 20%, and this reduction could be mitigated by reducing the pyrolysis temperature. The surface of recovered fibre remained clean and smooth, while the profile of elements and functional groups at the surface were similar to those of virgin fibres. The main gaseous products were CO, H2, CO2 and CH4, whilst the liquid product stream included phenolic and aromatic compounds.